Epithelial cell types and their proposed roles in maintaining the mucosal barrier in human chagasic-megacolonic mucosa - Koch, Christian; Da Silveira, Alexandre B. M.; De Oliveira, Enio C.; Quint, Karl; Neuhuber, Winfried; Brehmer, Axel; Jabari, Samir (Histochemistry and Cell Biology, 2017)
Patients suffering from chagasic megacolon must have an intact mucosal barrier as they survive this chronic disease for decades. A key structure of the mucosal barrier are epithelial cells. Vasoactive-intestinal-peptide (VIP)-positive nerve fibres are involved in influencing, e.g., epithelial cell proliferation, mucus secretion (e.g., mucin 2 and trefoil factor 3 of goblet cells) and inflammation or autoimmunity, all putative and/or known factors altered in chagasic megacolon. We analyzed qualitatively and quantitatively goblet cells, their specific markers, such as mucin 2 (MUC2) and trefoil factor 3 (TFF3) and enterocytes, the relation of VIP-immunoreactive nerve fibres to the epithelia, the distribution of gelsolin, a protein involved in chronic inflammation processes in the epithelia, and the proliferation rate of epithelial cells by combined 4',6-diamidino-2-phenylindole (DAPI) and phosphohistone-H3 (PHH3) staining. Goblet cells were the dominating epithelial cell type. They accounted for 38.4% of all epithelial cells in controls and changed to 58.9% in the megacolonic parts. In contrast to the overall expression in goblet cells of control epithelia, TFF3 was confined to goblet cells at the base of the crypts whereas MUC2 was found only in luminal goblet cells. Gelsolin-positive goblet cells were predominantly recognized within the controls. Finally, the mean value of mitosis increased from 1.5% within the controls up to 2.6% in the anal parts of the chagasic sepcimens. Taken together, increased cell proliferation, preponderance of goblet cells, differential MUC 2, and TFF 3 expression might all be factors maintaining an intact mucosal barrier within chagasic megacolon.
EVALuna2:35224